Bandpass filter design with spurious frequency reduction capability - Muda @ Ali, Rosnani (2014)
Passband microstrip coupled line filter are widely used in daily microwave engineering practice. There are various topologies to implement microstrip bandpass filters such as end-coupled, parallel coupled, hairpin, interdigital and combine filters. This thesis discusses design, simulation, fabrication and testing using microstrip technology. The choice of a parallel coupled filter topology is discussed and an application of the grooved substrate is presented to suppress the first spurious of Parallel Coupled Microstrip Bandpass Filter (PCMBF). Band pass filters (BPF) are significant role in wireless communication systems. These filters present an undesired pass band at twice the design central frequency of the filter. The narrowband with spurious suppression is achieved by using two stage PCMBF, BPF was designed by replacing the tight couplers are arranged at the input and output of the filter whist the weak couplers at the middle section of the tight coupler with optimize groove. By using Sonnet Lite software it shown the BPF with 2.99GHz cut off frequency and bandstop of to 7GHz has been simulated and fabricated on Flame Retardant 4 (FR4) substrate by using etching process. Significant spurious suppression up to 33.23dB is measured at 5.96GHz.